Decoupled distance–decay patterns between dsrA and 16S rRNA genes among salt marsh sulfate‐reducing bacteria. (8th April 2015) - Angermeyer, Angus; Crosby, Sarah C.; Huber, Julie A.
Summary: In many habitats, microorganisms exhibit significant distance–decay patterns as determined by analysis of the 16S rRNA gene and various other genetic elements. However, there have been few studies that examine how the similarities of both taxonomic and functional genes co‐vary over geographic distance within a group of ecologically related microbes. Here, we determined the biogeographic patterns of the functional dissimilatory sulfite reductase gene ( dsrA ) and the 16S rRNA gene in sulfate‐reducing bacterial communities of US East Coast salt marsh sediments. Distance–decay, ordination and statistical analyses revealed that the distribution of 16S rRNA genes is strongly influenced by geographic distance and environmental factors, whereas the dsrA gene is not. Together, our results indicate that 16S rRNA genes are likely dispersal limited and under environmental selection, whereas dsrA genes appear randomly distributed and not selected for by any expected environmental variables. Selection, drift, dispersal and mutation are all factors that may help explain the decoupled biogeographic patterns for the two genes. These data suggest that both the taxonomic and functional elements of microbial communities should be considered in future studies of microbial biogeography to aid in our understanding of the diversity, distribution and function of microorganisms in the environment.